(3ChQGb GdPgHs - (3HgGA GdedI hGdOjf GdaGefjfs
(3ChdgG (B:s
(3Efi CfG Ljc jG PG GdaVd hGdWhd aGNVV efG Ljc Hd QGLjc hGTQM HfhQc UOQi Md di YbdG hYbOI ef dSGfi jabghG bhdi s
(3BNQgG (B:s
(3hCMSf GdTYQ deG bjd CcPHg adjS HGdTYQ PG hGdZjQejGf dCf LedI eG bO bjd UGObI hGdbhd CMSf hGdbhGd MSGf s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdSGHYIs
(3GdfSNI HgG MhGTs
(3HgG CKGQ JbWjYs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeYI GdeQcRjI (B(1238) s
Keywords: (3GdCOHs